2019
DOI: 10.33396/1728-0869-2019-6-23-29
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota and Oxidative Stress in Patients With Metabolic Syndrome

Abstract: Aim: To study intestinal microbiota and the parameters of oxidative stress in patients with metabolic syndrome (MS). Methods: The sample consisted of 50 patients with MS aged 55-65 years and residing in Saint Petersburg. The reference group consisted of 129 individuals of similar age without MS. The quantitative and qualitative composition of parietal intestinal microbiota was studied by gas chromatography with mass spectrometry using microbial markers in plasma. Oxidative stress the final oxidation products o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, the microbiome and OS interaction in metabolic disorders [ 55 , 56 , 57 , 58 , 59 , 60 ], alcohol consumption [ 61 ], aging [ 62 ], and intestinal injury [ 63 ] have drawn attention. Although the number of studies in this field is rising every year, there are still many points to be clarified as well as unidentified molecules that might be relevant to this interaction.…”
Section: The Cooperation Of the Microbiome And Os In Disease Developm...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the microbiome and OS interaction in metabolic disorders [ 55 , 56 , 57 , 58 , 59 , 60 ], alcohol consumption [ 61 ], aging [ 62 ], and intestinal injury [ 63 ] have drawn attention. Although the number of studies in this field is rising every year, there are still many points to be clarified as well as unidentified molecules that might be relevant to this interaction.…”
Section: The Cooperation Of the Microbiome And Os In Disease Developm...mentioning
confidence: 99%
“…The authors added that there were no significant fluctuations in the number of Lactobacillus markers. At the end of the article, the authors reported the hypothesis that OS causes dysbiosis characterized by opportunistic pathogenic microbiota overgrowth [ 60 ].…”
Section: The Cooperation Of the Microbiome And Os In Disease Developm...mentioning
confidence: 99%